2020
DOI: 10.5935/2595-0118.20200011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of orofacial pain in wind instrument players

Abstract: BACKGROUND AND OBJECTIVES: This cross-sectional observational study was conducted due to the uncertainties that still exist about the role of playing wind instruments in musculoskeletal complaints. Therefore, the objective was to assess the prevalence of temporomandibular dysfunction and associated factors in wind instrument players. METHODS: Wind instrument players from the School of Music of Fine Arts of Paraná were evaluated for nine-months. Axes I and II of the Research Diagnostic Criteria for Temporomandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Of the 13 selected studies, three were conducted in Portugal, 6,19,21 two were carried out in Brazil, 23,27 and the remaining eight were conducted in Spain, 24 Korea, 20 Japan, 22 Poland, 26 Germany, 25 Holland, 28 Nigeria 29 and Chile 30 . Regarding the type of study, only one dissertation 19 and one course conclusion paper 30 were selected; the others were articles published in peer‐reviewed Journals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 13 selected studies, three were conducted in Portugal, 6,19,21 two were carried out in Brazil, 23,27 and the remaining eight were conducted in Spain, 24 Korea, 20 Japan, 22 Poland, 26 Germany, 25 Holland, 28 Nigeria 29 and Chile 30 . Regarding the type of study, only one dissertation 19 and one course conclusion paper 30 were selected; the others were articles published in peer‐reviewed Journals.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 31 25 to 1470 28 participants. Four articles 21,27,28,31 used the RDC/TMD diagnostic tool. Four studies using similar or RDC/TMD‐based tools were identified, these tools being the SQ‐TMD 22,26 and the Fonseca Questionnaire 6 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations